Media election survey 1994 - GP coverage of local election - Asp, Kent; Johansson, Bengt (University of Gothenburg, 2014)
The Media election surveys have been conducted since 1979 and covers news in radio, television and the metropolitan press, including the Svenska Dagbladet, Dagens Nyheter, the major tabloids, Rapport and Aktuellt. In 1994 a special study, when the newspaper Göteborgsposten and the coverage of local elections were studied alone in its own investigation. It also carried out a national survey, Media election survey 1994 (SND 0632).

Purpose:

To describe, identify and analyse the newspaper 'Göteborgspostens' reporting of the election campaign 1994.

Medievalundersökningarna har genomförts sedan 1979 och omfattar nyhetsrapporteringen i radio, tv och storstadspress, bland annat Svenska Dagbladet, Dagens Nyheter, de stora kvällstidningarna, Rapport och Aktuellt. 1994 genomfördes en specialstudie, då man studerade enbart Göteborgspostens bevakning av kommunvalet i en egen undersökning. Det genomfördes även en nationell undersökning, Medievalundersökningen 1994 (SND 0632) .

Syfte:

Att beskriva, kartlägga och analysera tidningen Göteborgspostens rapportering av valrörelsen 1994.
Medievalundersökningen 1994 - GP:s bevakning av kommunvalet
Keywords: mass media; massmedia; politics; politik; mass media exposure; massmediaexponering; local government policy; kommunalpolitik; newspaper press; nyhetspress; news; nyheter; internal politics; inrikespolitik; party politics; partipolitik; politicians; politiker; press; press; mass media coverage; massmediabevakning; Media; Media; POLITICS; POLITIK; Elections; Val; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap